Improvement of fish length estimates for underwater visual census of reef fish biomass. (16th January 2015) - Yulianto, I.; Hammer, C.; Wiryawan, B.; Pardede, S. T.; Kartawijaya, T.; Palm, H. W.
Summary Accuracy and precision are of great importance in the assessment of reef fish biomass when conducting an underwater visual census (UVC). Quantification and subsequent correction of the bias is required in order to standardize the estimates and correct for underwater distortion. To optimize the UVC, the observer should receive length‐measurement training in order to obtain in situ‐measurements that are as accurate and precise as possible. The objective of this study was to quantify the bias of fish length measurements made by divers with and without training in order to enhance reef fish biomass estimates. Adaptation of the diver to estimate fish lengths was analysed as a part of reef fish biomass monitoring in the Karimunjawa National Park, a national marine sanctuary in the Java Sea, Indonesia. Two divers practiced estimating a variety of fish in a natural environment by using styrofoam models attached to strings and sinkers. Analyses showed that by training the diver, his/her accuracy and precision improved substantially. Proving its reliability, an underwater visual census (UVC) becomes a useful and reliable method to assess the biomass of reef fishes.